Photographing the absent an installation of personal artifacts, light, and shadow as visual narrative of remembered memories about my mother - Adarayan, Emma Concepcion Apolinar
The shadow's formation is contingent with light. Similarly light is necessary for capturing a photograph. The shape and form of the things we see around us is the result of light from any luminous source. Light and its relevance in seeing and formation of images and shapes is examine to depict the absent through the process of photography. It mainly looks into the idea of drawing with light - occlusion, shadow projection and trace to represent the absent. As the artist grapples with the state of longing for a beloved departed, she utilizes the personal artifacts, the closest things that connect to her mother as an inspiration in remembering "what has been" in order to create visual narratives as a form of a memorial. The creative process also corresponds with ephemeral, the inability of the mind to hold vivid memories reiterated in the work by using phosphorescent substance capitalizing on its property that it sustains glow after it is exposed to light and subsequently dissipates. Although the process in the production of work is an expression of catharsis, the visual narratives is aimed to serve as a memorial through the process of photography. As a method, it aims to extend and reframe the idea of contemporary photography outside the boundaries of two-dimensional applications, to present rather in a manner of installation to engage the viewers to a more contemplative appreciation of the process related to remembering a memory.